Oxford Word Skills. Basic - Gairns R. Ruth (New York, Oxford University Press, 2011)
Basic for elementary and pre-intermediate learnersLearn the words you need to know at each level (Basic, Intermediate, and Advanced) See how the words and phrases are used in spoken and written English Practise using the vocabulary Revise what you've learnedImprove your vocabulary-learning skills Learn the words as preparation for the major exams